(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Let C : E → E be a bounded linear operator on a complex Banach space E and K : [0, +∞[→ C a locally integrable function. The aim of this paper, based on the theory of K- convoluted C-cosine functions, is to study the approximation theorem for K-convoluted C-cosine functions by showing the relation between the convergence of the sequence of C-resolvent and the exponentially bounded sequence of K-convoluted C-cosine functions.